Implikasi Yuridis Implementasi Inpres Nomor 1 Tahun 2022 Terhadap Pemenuhan Hak Jaminan Kesehatan Warga Negara - Emirza Nur Wicaksono (eScience Humanity Journal, 2026)
This study aims to analyze the legal implications of the implementation of Presidential Instruction Number 1 of 2022 on the optimization of the National Health Insurance Program (JKN) in fulfilling citizens’ rights to health insurance as part of constitutional rights in the 1945 Constitution of the Republic of Indonesia. The policy represents a government effort to strengthen the JKN program by increasing participation, improving compliance in paying contributions, and integrating BPJS Health membership with various public services. This research uses a normative juridical legal method with statutory and conceptual approaches. Legal materials were collected through literature studies, including laws and regulations, legal books, and relevant scientific articles. The data were then analyzed qualitatively using legal interpretation methods. The results show that Presidential Instruction Number 1 of 2022 aims to strengthen the sustainability of the JKN system and accelerate the achievement of universal health coverage in Indonesia. However, the policy that links BPJS Health membership to certain public services may create legal implications for citizens’ constitutional rights, particularly related to possible administrative barriers in accessing public services. In addition, the effectiveness of the policy is influenced by several factors, such as unequal access to health services, compliance in paying contributions, and the capacity of the health service system. Therefore, the optimization of the JKN program must be implemented proportionally while still considering the principles of the rule of law and the protection of human rights.